Sex differences in telomeres and lifespan in Soay sheep: From the beginning to the end. Issue 12 (June 2017) - Dantzer, Ben; Garratt, Michael
Abstract : There is tremendous diversity in ageing rates and lifespan not only among taxa but within species, and particularly between the sexes. Women often live longer than men, and considerable research on this topic has revealed some of the potential biological, psychological and cultural causes of sex differences in human ageing and lifespan. However, sex differences in lifespan are widespread in nonhuman animals suggesting biology plays a prominent role in variation in ageing and lifespan. Recently, evolutionary biologists have borrowed techniques from biomedicine to identify whether similar mechanisms causing or contributing to variation in ageing and lifespan in humans and laboratory animals also operate in wild animals. Telomeres are repetitive noncoding DNA sequences capping the ends of chromosomes that are important for chromosomal stability but that can shorten during normal cell division and exposure to stress. Telomere shortening is hypothesized to directly contribute to the ageing process as once telomeres shorten to some length, the cells stop dividing and die. Men tend to have shorter telomeres and faster rates of telomere attrition with age than women, suggesting one possible biological cause of sex differences in lifespan. In this issue of Molecular Ecology, Watson et al. (2017 ) show that telomere lengths in wild Soay sheep are similar between females and males near the beginning of life but quickly diverge with age because males but not females showed reduced telomere lengths at older ages. The authors further show that some of the observed sex difference in telomere lengths in old age may be due to male investment in horn growth earlier in life, suggesting that sexually dimorphic allocation to traits involved in sexual selection might underlie sex differences in telomere attrition. This study provides a rare example of how biological mechanisms potentially contributing to sex differences in lifespan in humans may also operate in free‐living animals. However, future studies using a longitudinal approach are necessary to confirm these observations and identify the ultimate and proximate causes of any sex differences in telomere lengths. Collaborations between evolutionary biologists and gerontologists are especially needed to identify whether telomere lengths have a causal role in ageing, particularly in natural conditions, and whether this directly contributes to sex differences in lifespan.